TLR Specific Immune Responses against Helminth Infections - Sivaprakasam Rajasekaran; Rajamanickam Anuradha; Ramalingam Bethunaickan (Journal of Parasitology Research)
Despite marked improvement in the quality of lives across the globe, more than 2 million individuals in socioeconomically disadvantaged environments remain infected by helminth (worm) parasites. Owing to the longevity of the worms and paucity of immunologic controls, these parasites survive for long periods within the bloodstream, lymphatics, and gastrointestinal tract resulting in pathologic conditions such as anemia, cirrhosis, and lymphatic filariasis. Despite infection, an asymptomatic state may be maintained by the host immunoregulatory environment, which involves multiple levels of regulatory cells and cytokines; a breakdown of this regulation is observed in pathological disease. The role of TLR expression and function in relation to intracellular parasites has been documented but limited studies are available for multicellular helminth parasites. In this review, we discuss the unique and shared host effector mechanisms elicited by systemic helminth parasites and their derived products, including the role of TLRs and sphingolipids. Understanding and exploiting the interactions between these parasites and the host regulatory network are likely to highlight new strategies to control both infectious and immunological diseases.